Determination of mercury in environmental samples in Muar river estuary - Rahman, Md. Mokhlesur; Kho, Hui Ling; Kasim, Zaleha; Wan Nik, Wan Sani (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2009)
This study was carried out at the Muar River Estuary, Johore, Malaysia. Water samples, sediment and biota that are Crassostrea iredalei, Perna viridis and Anadara granosa were collected during monsoon season in November 2005. All the samples were analyzed for the mercury concentration by using cold vapor atomic absorption spectrophotometer (CV-AAS). The temperature was between 28.70°C to 29.83°C, salinity at 12.78-29.96 ppt, dissolved oxygen at 5.0-6.83mg/L and pH at 6.71-7.93. The report of water samples show that the dissolved mercury in water samples was between 0.271μg L-1 and 0.8261tg L-1 while the total mercury in sediment was between 0.560-3.513μg g-1 dry weights. For biological sample, the average concentration of mercury in Crassostrea irredelei was 1.854 ± 1.012 μg g-1. Perna viridis was 0.366 ± 1.125 μg g-1 and Anadara granosa was 1.178 ± 1.182 μg g-1. The water at Muar River Estuary is still in safety level of mercury but biota especially Crassostrea irredelei and Anadara granosa are not safe to be taken due to the total mercury concentration was exceeding (WHO) level of 0.5 μg g-1.